قرآنی سیرت نگاری کے معاصر متنوع اسالیب : تجزیاتی مطالعہ (Al-Qamar, 2023)
In the last two centuries, the sīrah writes applied various methods and approaches to illustrate and interpret the events of the life of Holy prophet (PBUH) an authentic basis and respond to western critique. One of them is Qurʼanic Sirah writing and due to a variety of reasons, it emerged as trend during the course of twenty century. A plethora literature has been turning up on it that shows a diversity of styles has been adopted by prominent Qurʼanic Sirah writers to construct an authentic biography of the prophet Muhammad on the basis of Qurʼan. There are four prominent contemporary styles of the Qurʼanic sīrah Writing: Comprehensive, Subjective, Innovative and rotative. The present study is an endeavor to analyses works of the prominent Sirah Writer of this trend to analyses their distinctive elements of Qurʼanic sīrah writing. For these methods of analytical and context analysis applied that enable the readers to ascertain the distinctive features of each category and overview of the contemporary styles of Quranic Sirah writing.
Keywords: Sīrah Writing; Qur’anic Sīrah Writing; Modern Trends of Sīrah Writing; Contemporary Styles of Qur’anic Sirah Writing